Orkney snork nie! - Stephan Bouwer (Communicare)
In this article it is postulated that a critical/analytical reading of TV programmes should be an eclectic (or multi-disciplinary) transaction. With the "auteurism" viewpoint (vide Lapsley et all, Reader-response Criti cism (Allen et al) and the British Cul tural Studies (Birmingham) approach (Fiske et al) as point of departure, the popular Afrikaans sitcom ORK NEY SNORK NIE! (SABC TV1) is used as "vehicle" to demonstrate that TV viewing is a highly entangled, inter textual, communication transaction. The question of genre delimination, as an ideological implement, is also mooted. Two diagrammes (the nar ratological prose model and the "6 phase" communication model) are used as illustration to elucidate on encoding/decoding, with special emphasis on the contribution of the various sender collaborators and on author Esterhuizen as primary source of signification. With due allowance for the TV viewer as a reader who "negotiates" and "opposes", to use Althusser's terms, this article is an attempt at TV deconstruction in or der to demonstrate certain theories of pictorial communication and dis course analysis.